2017
DOI: 10.1038/s41598-017-03231-9
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 free fatty acids and all-trans retinoic acid synergistically induce growth inhibition of three subtypes of breast cancer cell lines

Abstract: All-trans retinoic acid (ATRA), one of vitamin A derivatives, shows greater growth inhibition of breast cancer cell for ER-positive than ER-negative cells, while triple negative breast cancer cell such as MDA-MB-231 cell is poorly responsive to ATRA treatment. In this study, we found that combination of ω-3 free fatty acids (ω-3 FFAs) and ATRA exhibited synergistic inhibition of cell growth in three subtypes (ER+ MCF7, HER2+ SK-BR-3, Triple negative HCC1806 and MDA-MB-231 cells) of human breast cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 56 publications
1
34
0
3
Order By: Relevance
“…Indeed, with EPA and DHA treatment for 3 days, downregulation of GPR120 by siRNA knockdown approach in breast cancer cells significantly increased cell growth inhibition in both MCF-7 and SKBR-3 cells but not MDA-MB-231 cells, indicating that v-3 PUFAs-induced breast cancer cell growth inhibition is independent of GPR120 receptor ( Figures 3A-1C). Furthermore, previous studies have revealed that v-3 PUFAs could inhibit mammary tumor progression via increasing cell apoptosis (Lin et al, 2017). To investigate whether GPR120 is also not involved in v-3 PUFAs-induced cell apoptosis.…”
Section: Gpr120 Is Not Involved In the Anti-tumor Effects Of V-3 Pufasmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, with EPA and DHA treatment for 3 days, downregulation of GPR120 by siRNA knockdown approach in breast cancer cells significantly increased cell growth inhibition in both MCF-7 and SKBR-3 cells but not MDA-MB-231 cells, indicating that v-3 PUFAs-induced breast cancer cell growth inhibition is independent of GPR120 receptor ( Figures 3A-1C). Furthermore, previous studies have revealed that v-3 PUFAs could inhibit mammary tumor progression via increasing cell apoptosis (Lin et al, 2017). To investigate whether GPR120 is also not involved in v-3 PUFAs-induced cell apoptosis.…”
Section: Gpr120 Is Not Involved In the Anti-tumor Effects Of V-3 Pufasmentioning
confidence: 99%
“…GPR120 was highly expressed in breast cancer cells and promoted breast cancer cell growth, however, which was opposite to the cell growth inhibitory effect of v-3 PUFAs in breast cancer cells. Furthermore, previous studies have revealed that v-3 PUFAs could inhibit mammary tumor progression via increasing cell apoptosis (Lin et al, 2017). Indeed, with EPA and DHA treatment for 3 days, downregulation of GPR120 by siRNA knockdown approach in breast cancer cells significantly increased cell growth inhibition in both MCF-7 and SKBR-3 cells but not MDA-MB-231 cells, indicating that v-3 PUFAs-induced breast cancer cell growth inhibition is independent of GPR120 receptor ( Figures 3A-1C).…”
Section: Gpr120 Is Not Involved In the Anti-tumor Effects Of V-3 Pufasmentioning
confidence: 99%
“…It has been largely reported that inflammation, recognized as a hallmark of cancer, is able to predispose tumor development and progression by well-orchestrated reciprocal interactions among cancer cells and surrounding stromal inflammatory cells within the tumor microenvironment. Several lines of evidence indicate that DHA and EPA, apart from their anti-inflammatory actions, have beneficial effects in cancer [76][77][78][79][80][81][82], suggesting their potential role either in cancer prevention or therapy. The main anti-neoplastic activities of n−3 PUFAs include the alteration of the composition of cell surface membrane and lipid raft disruption, the modulation of COX activity, the increased cellular oxidative stress, and the binding and activation of different receptors, including CBs, GPRs, TRVP1, and PPARs [83].…”
Section: N-acylserotonin Dha-5htmentioning
confidence: 99%
“…Cells were collected for fixation and stored at 4 • C prior to cell cycle analysis. The cells were then harvested with 70% ethanol, centrifuged, washed twice with PBS and then stained with a solution containing 100 µg/mL RNase A, 0.2% Triton X-100 and 50 µg/mL propidium iodide (Sigma-Aldrich, St. Louis, MO, USA) for 1 h at 4 • C in darkness before the cell cycle was measured with a flow cytometer within 1 h [39].…”
Section: Pi Staining Assaymentioning
confidence: 99%